A comment on Galperti and Strulovici (2017) - Asen Ivanov (Queen Mary University of London, School of Economics and Finance, 2021)
The analysis in Galperti and Strulovici (2017) relies on two axioms that appear normatively and descriptively very appealing. Notably, these two axioms, taken together with some standard axioms, imply a failure of dynamic consistency. The current comment argues that the two axioms are less normatively and descriptively appealing than they seem. Thus, the challenge to dynamic consistency posed by Galperti and Strulovici is less convincing than it first appears.
Keywords: D01; D60; D64; 330; intergenerational choice; intertemporal choice; dynamic consistency